Fakultas sastra Universitas Indonesia. Katalog induk naskah-naskah nusantara 3B - [Tidak Terdaftar] (Yayasan Obor, 1997)
Fakultas sastra Universitas Indonesia. Katalog induk naskah-naskah nusantara 3B